Anuran community of a coastal Atlantic Forest fragment in the state of Rio de Janeiro, southeastern Brazil - Martins, Angele (2014)
We conducted an anuran survey in a forest fragment of approximately 800 ha situated in the municipalities of Maricá, Saquarema, and Tanguá (22°52’ S; 42°40’ W; 20–450 m a.s.l., SAD69), in Rio de Janeiro state, Brazil, comprising matrices of dense ombrophilous forest and disturbed areas. This study aimed to render an inventory of the anuran species present in the area and provide data on spatial and temporal distribution, as well as natural history information on the species. Fieldwork was performed monthly between January 2011 and December 2012, during which anurans were sampled by means of Visual Encounter Surveys (VES) and 1 m2 plots. Total sampling effort was 411 man/hours (for VES) and 180 m2 of surveyed leaf litter (for plots). We recorded 44 species of frogs, with Hylidae being the most representative family. The VES method recorded an abundance of 2.8 individuals/hour, and plot sampling yielded an estimated density of 4 individuals/100 m2 . The species rarefaction curve did not reach an asymptote, indicating that an increase of sampling effort could still expand the number of recorded species. Our results reflect the relevance of the maintenance of this important and so far unprotected forest remnant in the state of Rio de Janeiro. The species richness found here indicates that the studied area, despite its small size, should be considered a priority area for amphibian conservation.